Climate Justice in Your Classroom - Anderson-Frey, Alexandra; Johnson, Brittany; Nuwer, Mikelle; Thompson, Luanne; Turner, Alex (Open textbook library., 2023)
As the inequitable impacts of climate change become more evident and destructive, it is essential for climate and environmental justice, as well as methods of civic engagement, to be taught at a high-level to college-level students. This book provides real examples of how professors at the University of Washington integrated these critical issues into their teachings, both in targeted lessons and as throughlines across an entire course. These samples of how environmental and climate justice have been successfully integrated into higher-level education can serve as both a record of the UW's progress towards centering JEDI at the heart of all students, and as a model for future instructors to use as they work to incorporate more aspects of justice and engagement into their own material.